Um levantamento sobre as práticas e percepções dos executivos financeiros sobre decisões de financiamento - Araújo, Mario Henrique Cerqueira de (2016)
The objective of this study was to identify financial executives’ practices and perceptions regarding financing decisions and compare them to the most important research in the field. In order to do so, it presents as a background both the main theories of capital structure, Trade-off and Hierarchy, and relates to previous studies and their findings. Questionnaires focused on mapping the most relevant factors of stock issuance or capital increase decision, determining the ideal level of indebtedness and choosing between long or short-term debt. Mapped data suggest executives’ preference for the usage of internal resources and debt. In addition, are relevant the level of interest rates, the disciplining effect of debt on management, and financial flexibility in setting adequate levels of indebtedness. It is worth mentioning the concern with the maintenance of liquidity when defining debt term. The sample composed of 54 financial executives suggests a preference for the Hierarchy theory in capital structure definitions. When contrasted to the other surveys there is correlation to only one of them, regarding the adequate level of indebtedness. Concerning the individual analysis of the factors, some similarities were found between the study and previous surveys. This study contributes for bringing a more up-to-date perspective of the data previously collected with Brazilian executives, as well as for elaborating a more comprehensive comparison between the main researches in the literature. In addition, it innovates when comparing the most relevant studies of the area through meta-analysis.